2021
DOI: 10.1088/1361-6528/ac0e67
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy engineering of TaO x -based resistive memories by Zr doping for improved variability and synaptic behavior

Abstract: Resistive switching (RS) devices are promising forms of non-volatile memory. However, one of the biggest challenges for RS memory applications is the device-to-device (D2D) variability, which is related to the intrinsic stochastic formation and configuration of oxygen vacancy (VO) conductive filaments (CFs). In order to reduce the D2D variability, control over the formation and configuration of oxygen vacancies is paramount. In this study, we report on the Zr doping of TaO x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The presence of oxygen vacancies in TaO x is characterized by X-ray photoelectron spectroscopy as shown in Figure S3c. The result contains a percentage of 16.68% in the nonlattice oxygen peak, which can be associated with the presence of oxygen vacancies. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of oxygen vacancies in TaO x is characterized by X-ray photoelectron spectroscopy as shown in Figure S3c. The result contains a percentage of 16.68% in the nonlattice oxygen peak, which can be associated with the presence of oxygen vacancies. , …”
Section: Resultsmentioning
confidence: 99%
“…The result contains a percentage of 16.68% in the nonlattice oxygen peak, which can be associated with the presence of oxygen vacancies. 31,32 2.3. Emulation of Synaptic Functions.…”
Section: Structure Of Oxide-based Synaptic Capacitor Andmentioning
confidence: 99%
“…Noted that our device is still large in size, e.g., 5 × 3 μm 2 , and by further reducing the device area, the number of peninsula structures in the device can be limited and the energy consumption of the device can be further reduced. We summarize our device performance, including the uniformity and switching time in comparison with other prototypical memristors in Figure c,d ,, (detailed data can be found in Table S1 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Skaja et al reported manifestation of reduced forming voltage and high R off /R on upon increasing V O s content in sputterdeposited Ta 2 O 5−x thin films, in which V O s concentration had been controlled by the sputter power and O 2 /Ar ratio [15]. Palhares et al reported on Zr doping in TaO x thin films as an efficient method of reducing V O s formation energy, increasing confinement of the CFs which led to reduced deviceto-device variability [16]. Ghenzi et al demonstrated that a small variation of O 2 /Ar ratio during reactive sputter growth of TiO 2−x -based devices led to different RS characteristics, e.g.…”
Section: Introductionmentioning
confidence: 99%